AN APPROACH TO CULTURAL TOURISTS’ SEGMENTATION IN POST-UNESCO COIMBRA - Carreira, Vivina Almeida; González-Rodríguez, M. Rosario; Díaz-Fernández, M. Carmen; Moutela, José Alberto (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2021)
This paper falls within the scope of cultural tourism studies, focusing on a World Heritage Site and intends to contribute to tourism literature by trying to better understand the differences between the tourists visiting it. A survey was conducted by self-administered questionnaires designed to identify different types of cultural tourists in post-UNESCO Coimbra (Portugal) so as to understand what they look for, the importance they assign to motivational factors, whether they are interested in participatory activities which call for cognitive, intellectual or affective engagement and their degree of satisfaction. A hierarchical cluster analysis was carried out based on age, education, family income, nationality, and length of stay. To perform this analysis of identification of homogeneous groups, Ward’s method and the Squared Euclidean distance were used as a measure of similarity. The variables were standardized to avoid bias due to the different scales. The results of this analysis allowed the identification of two groups. Chi-square analyses and Mann-Whitney U tests were also carried out for better characterizing the clusters. Results seem to be useful for destination managers to provide what tourists seek, to enhance their experiences and satisfaction, and strengthen this destination competitiveness and value creation.